The Influence of Students’ Learning Interest On The Economics Learning Achievement of 11th Grade Social Science Students At Semparuk Senior High School - Mashudi, Mashudi; Al Hidayah, Riama (International Journal of Educational Research & Social Sciences, 2025)
Education has several factors that can affect it, namely family, school, environmental, physiological, psychological, educator, students, material content, and methods used by educators in the teaching and learning process in the classroom. The purpose of this study is to describe: 1) The learning interest of 11th grade social science students at Semparuk SHS; 2) The learning outcomes of 11th grade social science students at Semparuk SHS; 3) The influence of students' learning interests on the economic learning outcomes of 11th grade social science students at Semparuk SHS. The research method uses a quantitative approach.  The location of the study was at Semparuk 1 SHS, with a research population of 96 respondents (students). The conclusions in this study are that 1) The learning interest of 11th grade social science students at Semparuk 1 SHS shows a very high category, 2) Learning outcomes are spread normally in general at the level of learning completeness and a small part of those who have not met the learning completeness, 3) The learning interest of 11th grade social science students at Semparuk 1 SHS has an effect on student learning achievement, where learning interest (X) increases by 1%, then learning outcomes (Y) will increase by 1.2% and the magnitude of the influence of learning interest on learning outcomes is 93.9% and the rest is influenced by other factors.